Endoplasmic Reticulum Chaperon Tauroursodeoxycholic Acid Attenuates Aldosterone-Infused Renal Injury - Honglei Guo; Hongmei Li; Lilu Ling; Yong Gu; Wei Ding (Mediators of Inflammation)
Aldosterone (Aldo) is critically involved in the development of renal injury via the production of reactive oxygen species and inflammation. Endoplasmic reticulum (ER) stress is also evoked in Aldo-induced renal injury. In the present study, we investigated the role of ER stress in inflammation-mediated renal injury in Aldo-infused mice. C57BL/6J mice were randomized to receive treatment for 4 weeks as follows: vehicle infusion, Aldo infusion, vehicle infusion plus tauroursodeoxycholic acid (TUDCA), and Aldo infusion plus TUDCA. The effect of TUDCA on the Aldo-infused inflammatory response and renal injury was investigated using periodic acid-Schiff staining, real-time PCR, Western blot, and ELISA. We demonstrate that Aldo leads to impaired renal function and inhibition of ER stress via TUDCA attenuates renal fibrosis. This was indicated by decreased collagen I, collagen IV, fibronectin, and TGF-β expression, as well as the downregulation of the expression of Nlrp3 inflammasome markers, Nlrp3, ASC, IL-1β, and IL-18. This paper presents an important role for ER stress on the renal inflammatory response to Aldo. Additionally, the inhibition of ER stress by TUDCA negatively regulates the levels of these inflammatory molecules in the context of Aldo.